Comparison of NOx for Diesel and Waste Cooking Oil Biodiesel - et. al., Adhirath Mandal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Transportation, industrial, commercial, agricultural and domestic sector mainly relies and uses diesel fuel to produce mechanical energy or power. Alternative fuels have also been introduced and using alternative fuels, continues to be a challenge. Biodiesel being a part of the alternative fuel, obtained from animal fat and vegetable oil, good alternative to conventional diesel. Popularity of biodiesel all of the world have recently increased because of its renewability, biodegradability, non-toxic, easy availability and better emission. For the use of biodiesel, engine modification is not needed. It is also free from Sulphur and aromatics, which helps in reducing exhaust emission, compared to conventional gasoline and also renders same fuel efficiency. For the use of biodiesel, engine modification is not needed. It is also free from Sulphur and aromatics, which helps in reducing exhaust emission, compared to conventional gasoline and also renders same fuel efficiency. Biodiesel could be blended in any ratio with the diesel and can also be used directly in the engine. Generally the price of raw edible oil are high and using them to produce biodiesel increase the price of the biodiesel. Biodiesel costs, 75-90% of the raw biodiesel. Because of the increasing cost of production of the biodiesel, use of waste cooking oil in the production of biodiesel would help in reducing the cost and would be a sustainable solution. It is sad that the waste cooking oil is discarded in the drain. Disposal of the waste cooking oil can lead to blockage, smell and environmental pollution. This paper simulates the NOx emission for Diesel and waste cooking oil biodiesel.